Ide bisnis usaha salad buah "Fresh Harvest" dalam meningkatkan kegiatan wirausaha dikalangan mahasiswa - Septiana, Nelly Afda; Himawati, Safiria; Fatursyah, Bima Ardia; Ahkam, M. Hafidhil (Maliki Interdisciplinary Journal, 2024)
Currently, the food and beverage sector in Indonesia is experiencing rapid growth. This industry shows interesting potential to be explored, becoming an interesting field to pursue. Based on BPS data for 2023, annual growth in the performance of the food and beverage industry reached 5.33%, making it the fourth largest growth among other processing industry subsectors. With increasingly busy lifestyles, many people now need additional food intake to maintain body health. Society is now trying to make consuming healthy food a habit to support body health. This is reflected in the selection of natural foods that are fresh and free from preservatives. One example of healthy food that is safe to consume is fruit salad. Currently, fruit salad has become a very popular food choice, especially products such as "Fresh Harvest," which has created a trend in Indonesia. One of the unique things about this fruit salad is the variety of flavors, making it popular among the public. This product has gone viral and received attention from various levels of Indonesian society. Fruit salad from "Fresh Harvest" is considered a recommended consumption choice because of its nutritional content which is important for today’s societal needs. Fruit salad is a food variant consisting of pieces of fruit served with mayo sauce, offering a delicious taste and freshness that is liked by various groups. Thus, this product not only meets nutritional needs, but also provides a satisfying culinary experience for consumers.